Optimization Strategy of Multi-microgrid Cooperative Operation Considering Carbon Trading and Renewable Energy Uncertainties - Jun ZHAO; Min ZHANG; Shifeng ZHANG; Qi YANG (Zhongguo dianli, 2023)
Vigorously developing renewable energy and continuously promoting carbon emission reduction have become important development directions of the power system. Since the current power system under the carbon trading mechanism does not fully consider the interest interaction between multiple entities and renewable energy uncertainties, this paper proposes a multi-microgrid cooperative operation optimization strategy considering carbon trading and renewable energy uncertainties. Firstly, the carbon quota and carbon trading mechanism are considered, and the microgrid model is established. The chance constraint method is adopted to consider renewable energy uncertainties. Then, according to the energy interaction mechanism between microgrids, the multi-microgrid cooperative operation model is established by using Nash bargaining theory and further decomposed into two sub problems that can be easily solved, namely, the multi-microgrid system revenue maximization and the profit distribution. The alternating direction multiplier method is used for distributed solutions to fully protect the privacy of each entity. Finally, the simulation results show that the proposed strategy can effectively reduce the carbon emissions of the system and improve the operating efficiency of each entity and have certain robustness.